Keanekaragaman spesies anggrek di jalur pendakian Cemara Kandang, Gunung Lawu, Jawa Tengah - Irvani, Muhammad Daffa; Susandarini, Ratna (Jurnal Biologi Udayana; Vol 26 No 2 (2022): JURNAL BIOLOGI UDAYANA, 2022)
Mount Lawu is an inactive volcano located on the border of Central Java and East Java. Geographical conditions that are between these two areas make Mount Lawu unique in its biodiversity. Orchid or familia Orchidaceae is a group of flowering plants with the second-highest species diversity with the number of species reaching of 25.000 worldwide. Several previous studies have shown that orchids in the Mount Lawu area are unique and have high diversity. Documentation of the diversity of orchids in the Mount Lawu area needs to be done as a first step in collecting data on potential flora and can be used as a basis for formulating orchid conservation policies. This research was conducted on the Mount Lawu Cemara Kandang Hiking Track, Karanganyar Regency, Central Java to take an inventory of the diversity of orchids along with their abundance and distribution along the Cemara Kandang Hiking Track. Research was conducted using the exploration method shows that along the Cemara Kandang Hiking Track there are 14 species of orchids. The fourteen species consist of Bulbophyllum schefferi , Bulbophyllum sect. Aphanobulbon , Bulbophyllum sp.1, Bulbophyllum sp.2 , Coelogyne miniata , Crepidium koordersii , L iparis montana , Microtis unifolia , Pholidota carnea , Pholidota globosa , Pinalia multiflora , Schoenorchis juncifolia , Taeniophyllum glandulosum , dan Thelymitra  javanica . The total abundance of orchids found in this study was 642 species and had a clustered distribution divided into two main zones along the hiking track.